RISET KOMUNIKASI ORGANISASI : DALAM PERSPEKTIF INTERPRETIF DAN KRITIS - Murwani, Endah (Universitas Prof. Dr. Moestopo (Beragama), 2006)
In the two decades, a growing number of researchers have used qualitative methods to study various aspects of organizational communication. In this article, we examine issues and challenges related to critique in qualitative research. Study of organizational communication, critical theory is concerned with the oppressive dimensions of corporate capitalism. These dimensions include hegemonic